The impact of poly-victimization on delinquency - Pires, Ana Rita Fonseca (2021)
Background: Research suggests that poly-victimization was a stronger predictor of delinquency, mediated by mental health problems. Experiencing several episodes of violence or neglect in multiple life contexts with many types of perpetrators is one of the principal causes of delinquency. The main objectives of this thesis are a) to analyze the impact of poly-victimization on delinquent behaviors in youth; and b) to compare the impact of poly-victimization between the normative young population and young offenders concerning anxiety and resilience. Methods: Four databases were systematically searched to identify relevant studies published. For the second article, 143 adolescents between 12 and 17 years old (M = 14.93, SD = 1.63), of which 97 (67.8%) were identified as young offenders and 46 (32.2%) as normative adolescents, answered the protocol. Results: Poly-victimization significantly increases the likelihood of engaging in delinquency. Offenders that were victims of poly-victimization showed higher psychological problems compared with other victims. Analysis showed a relationship between JVQ, the RS, and the STAIC C-2. Moreover, were founded differences between socio-demographic variables, poly-victimization, and delinquency. Conclusions: This data showed that poly-victimization has a higher impact on delinquency when compared to repeated exposure to the same type of violence or exposure to a single type of violence. Poly-victimization negatively affects resilience levels, reducing social and personal resources, and promotes anxiety in youth. Furthermore, our analyses showed that this phenomenon in childhood represents a significant risk for the development of delinquency.